Indigenous Collaboration for Leadership Development: A Canadian Example - Benson, Lyle; Enström, Rickard (Journal of Aboriginal Economic Development, 2019)
The purpose of this study is to describe how a Canadian provincial government department (Alberta Sport Council) collaborated with Indigenous communities, other government inter-agencies, corporate sponsors, and private business contractors in the creation, implementation, and measurement of the impact of an Indigenous youth leadership development program (also known as the Alberta's Future Leaders program or AFL). Based on the analysis of provincial government departments reports, input by government staff in previous reports, Indigenous youth leadership development program evaluations, reviews by the youth leadership development program creators and facilitators, and university research reports on the program, a collaborative consultative process emerged. The Dynamic Facilitating Process Model evolved to systematically describe the collaborative process that took place that recognized and promoted Indigenous consultation, consent, and involvement supporting Indigenous communities' priorities and protocols. The six phases in the Dynamic Facilitating Process that emerged are (1) Defining, (2) Designing, (3) Implementing, (4) Measuring, (5) Maintaining, and (6) Refining. Each of the phases in the model is clearly described with supporting collaborative examples with the different partners. Special attention was given to measure the impact of the youth leadership development program on Indigenous youth participants and to describe the impact of the youth leadership development program in Indigenous communities. This applied research and resulting model can serve as a guide for other governments and their inter-agencies, businesses, or other organizations that wish to engage in a positive collaborative process with Indigenous communities.